Tailored metal–ceramic nanocomposites prepared by redox cycling of polycrystalline Ni-doped yttria stabilized zirconia. (February 2016) - Morrissey, Amy; O'Brien, James R.; Reimanis, Ivar E.
Abstract: We demonstrate it possible to tailor unique metal–ceramic nanocomposites through redox cycling of Y2 O3 -stabilized ZrO2 containing 0.5 molar percent NiO (below the solubility limit). Upon the first reduction, Ni 2 + ions precipitate as metallic Ni 0 at pores, grain boundaries, or within the grain interiors with specific size ranges ( 5 nm/ 30 nm/ 200 nm) for each. Upon oxidation, Ni 2 + ions form, but their distribution is not the same as the original microstructure. In particular, NiO forms, and subsequent reduction leads to a distribution of metallic Ni different from that in the first reduction. One can ratchet the dissolution/precipitation behavior to form particular nanoscale arrangements. Graphical abstract: